Clinical and imaging characteristics of retinal neovascularization secondary to Behçet's uveitis - CHEN Xuelin; ZHANG Xiongze (Yanke Xuebao)
[Purpose:] To investigate the clinical and imaging characteristics of retinal neovascularization of the optic disc (NVD) and/or elsewhere in the retina (retinal neovascularization elsewhere, NVE) in eyes with Behçet's uveitis (BU). [Methods:] This retrospective analysis reviewed the clinical data and fundus imaging findings of patients diagnosed with BU complicated by NVD and/or NVE from January 2022 to September 2024. Imaging modalities included fundus photography, fluorescein fundus angiography (FFA), optical coherence tomography (OCT), and OCT angiography(OCTA). The study analyzed the correlation between the areas of NVD and/or NVE and the modified posterior segment inflammation scores, as well as retinal vascular leakage scores of the affected eyes. [Results:] The study included 27 patients (30 eyes) with an average age of 27.70 ± 12.58 years and a gender ratio of approximately 1:1. Bilateral NVD and/or NVE was observed in three patients (11%); 25 eyes (83%) had NVD, of which 17 eyes (57%) had only NVD and 8 eyes (27%) had both NVD and NVE. Two eyes (7%) showed areas of retinal non-perfusion, and seven eyes (23%)had concurrent vitreous hemorrhage. The average score for posterior segment inflammation on FFA was 20.93 ± 4.37, and the average score for vascular leakage was 7.57 ± 1.25. There was a significant positive correlation between the area of NVD and/or NVE and both the inflammation score (rs= 0.403, P = 0.027) and the vascular leakage score (rs = 0.518,P = 0.003). FFA and OCTA showed perfect agreement in detecting NVD and NVE (κ = 1.0). [Conclusion:] NVD and/or NVE in BU are not uncommon and are predominantly presented as NVD, mostly not associated with retinal non-perfusion, likely induced by inflammatory factors related to BU.